PENGARUH AKUNTABILITAS, KOMPETENSI MANAJERIAL, DAN INTEGRITAS TERHADAP EFEKTIVITAS KINERJA PEGAWAI (Studi pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Mojokerto) - Anggraeni, Wedha; Abdul Nasir, M. Jamal; Sofian, Octa Dwi; Sanjaya, Aprillina (JOURNAL AKSES STIA MALANG, 2026)
This study investigates the influence of accountability, managerial competence, and integrity on employee performance effectiveness at the Regional Financial and Asset Management Agency (BPKAD) of Mojokerto Regency, Indonesia. The research is motivated by BPKAD's strategic role in regional financial and asset governance, reflected by notable achievements such as receiving unqualified audit opinions (WTP) for ten consecutive years and the highest fiscal incentives in East Java. Despite these accomplishments, challenges remain in asset management and the implementation of information systems, indicating areas for improvement in employee performance. Using a non-experimental, correlational, and explanatory research design, data were collected via Likert-scale questionnaires distributed to all 51 BPKAD employees, employing a total sampling approach. Instrument validity was tested using Pearson's product-moment correlation, and reliability was assessed with Cronbach’s alpha. Classical assumption tests and multiple linear regression analyses were conducted using SPSS 26.0. Results show that accountability, managerial competence, and integrity significantly and simultaneously affect performance effectiveness. Individually, each variable also has a positive and significant effect. Among them, managerial competence has the most dominant influence. These findings highlight the critical role of enhancing managerial capabilities and ethical values to improve public sector performance, offering empirical support for organizational development initiatives within local government institutions.